EFEKTIVITAS PROSEDUR REKRUTMEN PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH KABUPATEN BANGGAI - Samba’a, Nikita Anastasya (JURNAL ADMINISTRASI PUBLIK, 2018)
Recruitmen officer is processing looks for, finds and to describe the applicantsappropriate to be officer in and by an institution. In execution of procedure recruitmen ingeneral there is still existence of formation that is still empty after performed by processrecruitmen. The goal of this research is to describe the effectiveness of civil official’srecruitment procedure in Kabupaten Banggai Official Region Council (Badan KepegawaianDaerah Kota Kabupaten Banggai). By the recruitment procedure which is run, it is expectedto be able to fulfil officials’ needs. Besides, it is also expected to get the officials which areappropriate with the qualifications in every position will be achieved by official candidates.Key word : Effectiveness Recruitment Procedur